A STUDY ON FOREIGN DIRECT INVESTMENT IN INDIA - Dr. P. Sai Rani, Sourav Kumar Ghosh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Indian economy is one of the fastest emerging economies of the world which attracts a remarkable amount of foreign direct investments every year. However, there have been reports for the past few years showing inconsistency in inflows of foreign direct investment in India and also the GDP of India is observed to be in decreasing trend. This gives rise to the need of studying multiple facets of such investments. This paper aims at studying the trends of FDI inflows in India and ascertaining the country-wise FDI inflows and sector-wise distribution of such investments in the country. This study is based on secondary data collected from various reliable sources. Simple statistical tools like CAGR (Compound Annual Growth Rate), and Percentage have been used for purpose of study. The study reveals varying trends of FDI inflows in India in the recent years which is in line with the world economy but it is generally on a rising side. The study also reveals that Mauritius has been the top investing nation in India and among all the sectors the service sector attracts the maximum FDI from various nations over the period of study. The data collected for the purpose of study is limited to almost last two decades and is entirely based on Indian economy only.